Multiple characterization of some glassy-alloys as photon and neutron shields: in-silico Monte Carlo investigation - Perişanoğl, U.; El-Agawany, F. I.; Tekin, H. O.; Kavaz, E.; Zakaly, Hesham M. H.; Issa, Shams A. M.; Zaid, M. H. M.; Sidek, H. A. A.; Matori, K. A.; Rammah, Y. S. (IOP Publishing, 2021)
In the present work, the nuclear radiation shielding proficiency of eight glassy alloys(Gd25RE25- Co25Al25 (RE = Tb, Dy and Ho)) containing different amounts of rare earth elements was investigated with MCNPX simulation codes. Mass attenuation coefficients(μ/ρ) of the glassy alloys were simulated in the energy interval of 0.2–20 MeV by exploiting MCNPX codes, and the generated data were found to match with theoretical WinXCOM results. Next, other crucial photon attenuation parameters, effective atomic number(Zeff), Half Value Layer(HVL), and Mean Free Path (MFP), were gotten out using μ/ρ values. It was seen that Er20Tm20 and Er20Tb20 samples replaced with Er by Gd had the highest Zeff and μ/ρ values, whereas HVL and MFP values were the smallest among the other glassy alloys. Geometric progression (GP) procedure was enjoyed to achieve the exposure and energy absorption buildup factors(EBF and EABF)for the glassy alloys proposed. EABFs and EBFs took the largest and lowest values for Gd25Tb25 and Er20Tm20, respectively, to the other samples. Furthermore, the glassy alloys’ neutron reduction abilities were estimated by acquiring fast neutron removal cross-sections(∑R). It was noticed that the ∑R values of the glassy alloys are increased with the rising sample density and seen to be comparable to ∑R values of water and ordinary concrete. The results obtained from this study are important in that they show that glassy alloys can be used as radiation shielding.